Ekstraksi benda asing gigi palsu di esofagus dengan esofagotomi servikal - Cahyono, Arie; Hermani, Bambang; Hadjat, Fachri; Rahman, Sukri (Oto Rhino Laryngologica Indonesiana, 2012)
Background: Foreign body in the esophagus should be removed as soon as possible under optimal conditions to prevent complications. Esophagoscopy is a safe and effective procedure for foreign bodies removal in most cases, but in some cases esophagoscopy could not be performed or failed to extract the foreign body, necessitating surgery such as esophagotomy. Objective: To illustrate the cervical esophagotomy technique as a management of esophageal foreign bodies. Case: A 53-years old woman with a foreign body (dentures) in the esophagus that failed to be removed by esophagoscopy and need cervical esophagotomy. Management: Cervical esophagotomy was performed after esophagoscopy failed to remove the foreign body. Conclusion: Cervical esophagotomy is needed in cases of esophageal foreign body in which of esophagoscopy could not be performed or failed to remove the foreign body. Keywords : foreign body, denture, esophagus, cervical esophagotomy  Abstrak :  Latar Belakang: Benda asing di esofagus harus sesegera mungkin dikeluarkan dalam kondisi yang optimal untuk mencegah terjadinya komplikasi. Esofagoskopi adalah cara yang aman dan efektif untuk ekstraksi benda asing pada sebagian besar kasus, namun pada beberapa kasus tindakan esofagoskopi tidak dapat dilakukan atau gagal mengeluarkan benda asing, sehingga diperlukan tindakan bedah berupa esofagotomi. Tujuan: Kasus ini diajukan untuk mengilustrasikan teknik esofagotomi servikal sebagai penatalaksanaan benda asing esofagus. Kasus: Dilaporkan satu kasus wanita 53 tahun dengan benda  asing gigi palsu di esofagus yang gagal dikeluarkan dengan esofagoskopi sehingga diperlukan tindakan  esofagotomi servikal untuk mengambilnya. Penatalaksanaan: Dilakukan esofagotomi servikal setelah esofagoskopi gagal mengeluarkan benda asing. Kesimpulan: Esofagotomi servikal dilakukan untuk mengeluarkan benda asing di esofagus apabila tindakan esofagoskopi tidak dapat dilakukan atau gagal mengeluarkan benda asing. Kata kunci : benda asing, gigi palsu, esofagus, esofagotomi servikal.